The mechanism of the social state and the place of the pension system in it: theoretical and legal aspects (Law and Safety, 2024)
The article is devoted to the theoretical and legal study of the role and place of the pension system in the mechanism of the social state on the example of the modern Ukrainian legal experience. Based on the analysis of legislation, doctrinal positions and practice of the Constitutional Court of Ukraine, the author has formulated the own vision of the substantive and ontological core of pension provision. It is demonstrated that pension provision as a set of legal relations and a real legal phenomenon in the substantive and ontological dimension cannot be identified either with the process of providing an individual with a set of certain social and material services (procedural approach), or with a set of measures taken by the State to meet the needs of an individual for adequate material security upon reaching retirement age or due to adverse social circumstances which exclude their opportunities for active participation in economic and social life. According to the human-centred paradigm, the substantive and ontological essence of pension provision is not only the right (legal possibility) to demand from the state a certain level of pension payments in accordance with certain objective criteria, but also the real possibility to receive such payments in the amount that allows a person to maintain a decent existence, to ensure their key needs in life and social environment, avoiding poverty and social isolation.The importance of the State’s guarantee of the right to pension as a component of the constitutional right to social protection is substantiated. It has been revealed that the social state implements such a social policy which guarantees not only pension payments, but also their amount, frequency of receipt and indexation in accordance with the established procedure, which ensure that every person entitled to a pension has an adequate standard of living, the stability of the established standards of pension provision, the guarantee of this provision, the predictability of the legislative policy of pension provision (in accordance with the concept of legitimate expectations), and the appropriate law enforcement policy of pension provision. It has been proved that in the context of the social state concept, the problem of legislative fixation of the optimal model of pension provision (which would take into account the issues of determining the amount of pension provision, their ranking in various, including special, laws, methods and pace of pension indexation, etc.), taking into account the economic situation of the State and the compliance of such provision with the task of realisation of basic human needs for decent living conditions, requires careful consideration (in accordance with the concept of “space for consideration”). The article emphasises that compliance with the constitutional principles of the social state requires legislative regulation of pension provision on the basis of equity and proportionality, taking into account the State’s obligation to ensure decent living conditions for every citizen of Ukraine.
Keywords: human rights; human centrism; decent living conditions; pension provision; social state; social policy; equity; proportionality.